Cirque du Freak. Volume 2, The vampire's assistant - Shan, Darren (Yen Press, 2009)
A manga adaptation of "Cirque Du Freak," in which Darren agrees to become Mr. Crepsley's assistant and turns into a half-vampire; but while he makes friends at the Cirque du Freak, he struggles with his urges to drink human blood.